2004
DOI: 10.1002/j.1939-4640.2004.tb02764.x
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality of Men With Asymptomatic Chlamydial Infection

Abstract: We have shown previously that the in vitro exposure of spermatozoa to elementary bodies (EBs) of Chlamydia trachomatis can lead to sperm death over a number of hours of incubation. As such, we have hypothesized that the ejaculates of men with a chlamydial infection could contain increased numbers of nonmotile (dead) spermatozoa if they are exposed to EBs prior to ejaculation. To test this hypothesis, the ejaculates of 642 men undergoing diagnostic semen analysis as part of ongoing infertility investigations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 44 publications
5
70
0
3
Order By: Relevance
“…Our study found CT DNA in semen from 2.5% of infertility patients, with copy numbers ranging from 8,300 to 590,000. This prevalence rate is consistent with earlier publications (32,75,76). CT DNA was associated with a significant decrease in neutral α-glucosidase concentration (and a trend towards lower total sperm and total motile sperm counts).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found CT DNA in semen from 2.5% of infertility patients, with copy numbers ranging from 8,300 to 590,000. This prevalence rate is consistent with earlier publications (32,75,76). CT DNA was associated with a significant decrease in neutral α-glucosidase concentration (and a trend towards lower total sperm and total motile sperm counts).…”
Section: Discussionsupporting
confidence: 92%
“…However, CT, an intracellular parasite which is the most prevalent sexually transmitted bacterial pathogen in industrialized nations (31), has been associated with LCS. A recent study utilizing nested plasmid polymerase chain reaction (PCR) found both significantly higher seminal WBC concentrations and a greater prevalence of LCS in men who were positive for CT DNA (32).…”
Section: Introductionmentioning
confidence: 99%
“…This assay (LCR) may not be appropriate for the detection of C. trachomatis in semen, which may be due to the fact that semen might contain inhibitory components that interfere negatively with the LCR. However, a recent report by Hosseinzadeh et al (2004) who used the LCR as a confirmatory test for in-house PCR, showed a good correlation between these methods of testing semen.…”
Section: Discussionmentioning
confidence: 99%
“…serology versus molecular methods); as well as variable and sometimes inadequate methods to assess semen quality. More recent studies (Hosseinzadeh et al, 2004;Bezold et al, 2007;Al-Mously et al, 2009), using molecular methods to detect infection, and robust methods of laboratory andrology to examine semen, have generally found that men with a current infection of C. trachomatis have poorer quality ejaculates compared than men who do not. It is unclear whether this is because of reduced levels of spermatogenesis in the presence of the bacterium, or whether infection causes an altered ejaculatory response.…”
Section: Infertilitymentioning
confidence: 99%